2022
DOI: 10.1111/andr.13258
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA biomarkers in cancers of the male reproductive system: Are we approaching clinical application?

Abstract: Background: Specific cancer types face specific clinical management challenges.Owing to their stability, robustness and fast, easy and cost-effective detection, microRNAs (miRNAs) are attractive candidate biomarkers to the clinic.Objectives: Based on a comprehensive review of the relevant literature in the field, we explore the potential of miRNAs as biomarkers to answer relevant clinical dilemmas inherent to cancers of the male reproductive tract (prostate [PCa], testis [TGCTs] and penis [PeCa]) and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 126 publications
(275 reference statements)
0
7
0
Order By: Relevance
“…[58][59][60] One of the major drawbacks is that teratoma secretes low levels of circulating miRNA and cannot provide clinical utility. 61,62 Hemolysis may affect the measurements, which demands refinement in the laboratory techniques. In addition, laboratory quality controls and proper validations are required to implement this assay for clinical utilization.…”
Section: Cisplatin Resistance In Germ Cell Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60] One of the major drawbacks is that teratoma secretes low levels of circulating miRNA and cannot provide clinical utility. 61,62 Hemolysis may affect the measurements, which demands refinement in the laboratory techniques. In addition, laboratory quality controls and proper validations are required to implement this assay for clinical utilization.…”
Section: Cisplatin Resistance In Germ Cell Tumorsmentioning
confidence: 99%
“…In the liquid biopsy studies, miR-371–373 showed better sensitivity than serum biomarkers ie, AFP, HCG, and LDH to detect postchemotherapy residual disease and recurrence 58–60 . One of the major drawbacks is that teratoma secretes low levels of circulating miRNA and cannot provide clinical utility 61,62 …”
Section: Germ Cell Tumors Not Derived From Gcnismentioning
confidence: 99%
“…MiR-371a-3p is part of a cluster located at chromosome 19, which includes 3 miRNAs: miR-371a-3p, mir-372-3p and miR-373-3p [20][21][22]. The cluster's members are specifically expressed in human embryonic stem cells (ESCs) and have been widely studied as potential TGCT biomarkers, being first suggested in 2011 [21,23]. The most promising miRNA of the three is miR-371a-3p.…”
Section: Mir-371a-3p In Germ Cell Tumorsmentioning
confidence: 99%
“…In this special issue, we learn more about how miR‐371a‐3p may be used in clinical diagnosis, 13 and how useful it is to predict whether a germ cell tumor is still present after retroperitoneal lymph node dissection in patients with pure seminoma 14 . Finally, we learn how miR‐515‐5p is modulated by a long non‐coding RNA in prostate cancer, 15 and we get an overview on the status of miRNA‐based biomarkers among urological cancers 16 . Outside an oncological setting, we also learn about the sncRNA profiles in the seminal plasma of men with azoospermia and poor semen quality 17–19 …”
mentioning
confidence: 99%
“…14 Finally, we learn how miR-515-5p is modulated by a long non-coding RNA in prostate cancer, 15 and we get an overview on the status of miRNA-based biomarkers among urological cancers. 16 Outside an oncological setting, we also learn about the sncRNA profiles in the seminal plasma of men with azoospermia and poor semen quality. [17][18][19] Several miRNAs have also been considered as therapeutic targets, and the number of clinical trials, including the administration of specific miRNAs or anti-miRNAs, is growing.…”
mentioning
confidence: 99%